Utility of sample entropy from intraoperative cerebral NIRS oximetry data in the diagnosis of postoperative cognitive improvement - Wang, Xiaoxiao; Huo, Ran; Yuan, Wanzhong; Yuan, Huishu; Wang, Tao; Li, Nan (Frontiers in Physiology, 2022)
Background: Appropriate monitoring and early recognition of postoperative cognitive improvement (POCI) are essential. Near-infrared spectroscopy (NIRS) showed the predictive potential of POCI. Non-linear dynamical analysis is a powerful approach for understanding intraoperative regional cerebral oxygen saturation (rSO2). Objective: We hypothesized that the sample entropy (SampEn) value of intraoperative rSO2 has the potential to predict POCI. Methods: This retrospective cohort study was conducted from June 2019 and December 2020 in a tertiary hospital in Beijing, China. A total of 126 consecutive patients who underwent carotid endarterectomy (CEA) were screened. 57 patients were included in this analysis. The primary outcome was the diagnostic accuracy of rSO2 for the prediction of POCI. Results: 33 patients (57.9%) developed POCI on postoperative day. The SampEn values of rSO2 were significantly higher in the POCI group (P<0.05). SampEn remained an independent predictor of POCI in multivariate analysis. The area under the ROC curve (AUC) value of SampEn of rSO2 for POCI were 0.706 (95% CI, 0.569–0.843; P=0.008). Addition of preoperative MoCA assessment and blood pressure-lowering treatment increased the AUC to 0.808 (95% CI, 0.697–0.919; P < 0.001). Conclusions: The SampEn value of rSO2 showed promise as a predictor of POCI. Non-linear analysis could be used as a supplementary method for intraoperative physiological signals.